Memperkuat Pengelolaan Data Ad Hoc: Penilaian Kemampuan COBIT 2019 terhadap Platform Statistik Provinsi - Tambalean, Feergio Given Majesty; Montolalu, Chriestie Ellyanne Clara Juliet; Takaendengan, Mahardika Inra; Lapihu, Dodisutarma; Soewoeh, Christian Alderi Jeffta; Tenda, Edwin (Universitas Komputer Indonesia, 2026)
Decentralized public sector information systems frequently exhibit operational vulnerabilities due to fragmented IT governance practices, undermining data reliability and public service delivery. This study evaluates the governance maturity of a Public Data Dissemination Platform operated by a regional statistical office to establish a standardized capability baseline. Employing a descriptive quantitative design, the research applies the COBIT 2019 framework across the Deliver, Service, and Support (DSS) and Monitor, Evaluate, and Assess (MEA) domains. Data were collected through semi-structured interviews, system observation, and archival documentation, then quantified using CMMI-aligned capability scoring and calibrated gap analysis. Empirical findings reveal that both domains operate at Level 1 (Performed Process), with aggregate scores of 1.16 for DSS and 0.75 for MEA. The most critical deficiencies occur in incident management (DSS02, Gap = 3) and external compliance monitoring (MEA03, Gap = 3), while assurance mechanisms (MEA04) remain entirely unestablished at Level 0. These results indicate that current operations rely on ad hoc procedures rather than standardized controls. Consequently, the study provides a phased remediation roadmap prioritizing formal documentation, structured service tracking, and independent evaluation functions. The framework offers a replicable diagnostic model for subnational agencies seeking to transition from reactive maintenance to predictable, audit-ready IT governance.